PERANCANGAN VIDEO PROMOSI KOLAM IKAN SAKTI SUNGAI JANIAH DI KABUPATEN AGAM - IIM KURNIA, Dr. Syafwandi, M.Sn., Riri Trinanda, S.Pd., M.Sn. (DEKAVE : Jurnal Desain Komunikasi Visual, 2019)
Sakti Sungai Janiah Fish Pond is a tourist attraction in West Sumatra Province. Sakti fish attraction has long been famous, the fish in the pond according to legend originated from humans, but in recent years visitors who have arrived have begun to decrease due to the many new tourist objects opened, this situation makes the authors interested in improving returning the number of visitors in the magical fish attraction by making a promotional video entitled